Soft Robotics: Increasing the Dimensionality of Soft Microstructures through Injection‐Induced Self‐Folding (Adv. Mater. 38/2018). Issue 38 (17th September 2018) - Ranzani, Tommaso; Russo, Sheila; Bartlett, Nicholas W.; Wehner, Michael; Wood, Robert J.
Abstract : In article number1802739, Tommaso Ranzani and co‐workers introduce a manufacturing method that combines multilayer soft lithography, precision laser micromachining, and injection‐induced self‐folding to establish a new paradigm for creating 3D soft microstructures and devices. To demonstrate the potential of this process, they present a 12‐layer soft robotic peacock spider with embedded microfluidic circuitry and actuatable features. Image credit: Second Bay Studios.